Exploring How Emotional Intelligence Contributes to Virtual Teams: Interpretive Analysis of a Phenomenological Study - Quisenberry, William L. (European Scientific Journal, ESJ, 2018)
The use of virtual teams continues to rise due to various factors such as increased pressure from competing forces, globalization, the need for improved efficiency, and technological advances. Despite the various benefits associated with high performing virtual teams, these specialized groups also experience extremely high failure rates. The increased failure can come as a result of various challenges including a lack of knowledge-sharing, limited communication, team members who lack self-managed and virtual teaming experience, and social loafing. While increased challenges are prevalent during virtual teaming arrangements, there seems to be evidence supporting that virtual team performance can be improved when team members have higher emotional quotients. This paper explores the potential benefits of emotionally intelligent virtual team members to understand how those with higher emotional quotients can potentially improve project success. The research involved analyzing a phenomenological study that interviewed 31 self-managed virtual team members via electronic questionnaires and surveys. This study follows up the original empirical research with an interpretative analytical review of the phenomenological findings pertaining to emotional intelligence and virtual teams. A thorough discussion regarding the findings and recommendations are provided.